Effects of roughness geometry on heat transfer, fluid flow and thermo-hydraulic performance of solar air heaters: A comprehensive review - Mondloe, Dilbag Singh; Ghritlahre, Harish Kumar; Agrawal, Gajendra Kumar; Rathore, Kamini; Naik, Hemant; Parmar, Onika (Archives of Thermodynamics, 2026)
In the present review article, an effort has been made to review various experimental and numerical research, which include heat transfer rate and fluid flow characteristics of a modified solar air heater (SAH) using various artificial roughness. As it is clear that artificial roughness enhances the heat transfer and performance, in this review study, various types of roughened SAH performances have been examined. These various roughness patterns are V-shape, W-rib, arc shape, spherical ball and S-type, and their placement arrangements, like transverse, inclined and longitudinal, are discussed in this article. The comparative studies of thermo-hydraulic performance with heat transfer and fluid flow investigations of various roughened SAHs have been described to identify optimal performance parameters to select the optimum configuration that can be further used for various applications. In addition to this, various correlations of the Nusselt number and friction factor developed by various investigators have also been reported. The main aim of this study is to evaluate the SAH performance using various roughness patterns. It also provides several essential recommendations for effectively designing and implementing SAHs. This review encompasses a comprehensive analysis of 178 research articles published between 1988 and 2024, focusing on advancements in the field. The findings showcase the peak values for the Nusselt number as 7.61, the friction factor reaching 6.48 times that of a smooth duct for discrete multiple-arc ribs, and the maximum thermal-hydraulic performance reported at 4.73 for dimple or protrusion ribs.